Oral Health and Cardiac Rehabilitation: A Scoping Review - Ab Malik, Normaliza; Mohamad Yatim, Saari; Li , Leonard Sheung Wai; Abdullah Ramaiah , Asri Rangga (IIUM Medical Journal Malaysia, 2022)
This scoping review aimed to gain an insight into the oral health status, behaviour, knowledge, and risk among cardiovascular patients, as well as to explore challenges and to make a recommendation concerning oral health and cardiovascular patients. It focused on four key areas, namely oral health status, behaviour, knowledge, and associated risk factors. Relevant studies were searched using a combination of keywords and related search terms. Four available databases were used; EBSCOhost, Scopus, Proquest, and Pubmed to identify the relevant studies. A total of 789 papers were screened and duplicated papers were removed, 28 papers were retrieved for full-text review. It was found that most cardiovascular patients have poor oral health, while their oral health behaviour and knowledge were at a fair level. There are a limited number of studies assessing oral health conditions during cardiac rehabilitation. In general, protocol and guidelines about the importance of oral health care for cardiovascular patients are still lacking. Having good oral health has potential impacts in reducing the risk of CVD. Future research is warranted with potential intervention approaches to improve oral health conditions among cardiovascular patients, thus reducing the risk of CVD.